JOURNAL OF GOVERNMENT & POLITICS : The Implications of gated Society in Jakarta Metropolitan Region : A Multiple-Case Study in Tangerang District, Banten, Indonesia - Indah Surya Wardhani (FISIPOL UMY, 2016)
This paper argued taht the gating system intensifies existing divergence of the gated communities and the kampung communities.